The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.16888/interd.2020.37.2.8
|View full text |Cite
|
Sign up to set email alerts
|

El rol de la atribución en el comportamiento prosocial adolescente

Abstract: La prosocialidad comprende aquellas conductas intencionales que se realizan para el beneficio de otras personas. Entre las variables que tienen una incidencia en la decisión de ayudar, se incluyen los patrones atribucionales: interpretaciones que se realizan sobre las causas de un determinado acontecimiento. El objetivo de este trabajo fue evaluar el rol que tiene la atribución que un individuo realiza sobre una situación de potencial ayuda en la elicitación de la conducta prosocial. A partir de un muestreo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(34 reference statements)
1
1
0
3
Order By: Relevance
“…In this dimension, no gender differences were detected, and as in the previous dimension, participants' not being a volunteer and having people under their care had a considerable influence on the results. This confirms the study by Balabanian and Lemos (2020) and their idea that mental models based on beliefs about the world have a decisive influence on prosocial tendencies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this dimension, no gender differences were detected, and as in the previous dimension, participants' not being a volunteer and having people under their care had a considerable influence on the results. This confirms the study by Balabanian and Lemos (2020) and their idea that mental models based on beliefs about the world have a decisive influence on prosocial tendencies.…”
Section: Discussionsupporting
confidence: 89%
“…Shame was moderately associated with antisocial behaviour. Balabanian and Lemos (2020), in their study on attributional patterns among adolescents, confirmed the idea that mental models based on beliefs about the world have a decisive influence on the tendency to be prosocial. They found that those who chose internal, controllable factors as their causal explanation were less likely to be prosocial, since attributing responsibility for the situation to the subject who suffers from it would have an unfavourable effect on the performance of helping actions.…”
Section: Introductionmentioning
confidence: 67%
“…El aspecto del comportamiento prosocial con mayor prevalencia fue la conducta prosocial con 3,65 similar a los resultados encontrados en adolescentes escolarizados con discapacidad intelectual leve en donde se evidencian altos niveles de prosocialidad en los sujetos estudiados, seguido de la empatía y apoyo emocional (Montiel y González, 2021). Además se encontró un estudio desarrollado en 359 adolescentes argentinos de clase media, el cual corrobora con los resultados obtenidos sobre la conducta prosocial alta (Balabanian et al, 2020), sin embargo en un estudio realizado en Colombia con un grupo de adolescentes desvinculados de grupos armados, menciona que los aspectos de empatía y apoyo emocional presentaron mayor incidencia que la conducta prosocial (Gómez Tabares, 2019).…”
Section: Discussionunclassified
“…Mientras que el comportamiento prosocial se define como la tendencia a realizar acciones que buscan un efecto beneficioso sobre los demás y pertenece al ámbito de los hábitos, las prácticas y el modo común de interacción social. Algunos autores mencionan que el verdadero comportamiento prosocial es aquel en donde la ayuda que brinda una persona es aquella que no tiene motivación de ningún tipo, por lo tanto no hay recompensa material o extrínseca (Correa Duque, 2017;Balabanian et al, 2020).…”
Section: Introductionunclassified
“…Mientras que el comportamiento prosocial se define como la tendencia a realizar acciones que buscan un efecto beneficioso sobre los demás y pertenece al ámbito de los hábitos, las prácticas y el modo común de interacción social. Algunos autores mencionan que el verdadero comportamiento prosocial es aquel en donde la ayuda que brinda una persona es aquella que no tiene motivación de ningún tipo, por lo tanto no hay recompensa material o extrínseca (Correa Duque, 2017;Balabanian et al, 2020).…”
Section: Introductionunclassified